2021
DOI: 10.12688/f1000research.51219.2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lactic acid bacteria and yeasts as probiotics on the growth performance, relative organ weight, blood parameters, and immune responses of broiler: A meta-analysis

Abstract: Introduction: The number of publications in Scopus on this topic increased from less than 50 in 1995 to more than 250 in 2015. In other hand, inconsistency in results about the correlation between yeast and lactic acid bacteria as probiotics has been evident since the early publications on use in broilers. Methods: A meta-analysis was conducted to determine relationship between lactic acid bacteria and yeast as probiotics to broiler diets on the growth performance, relative organ weight, blood parameters, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The current study found that the addition of PC to the diet significantly increased the spleen index of AA+ broilers compared to the control group, and that the increase in thymus and bursa indices did not reach significant levels. This was also similar to the findings of Sjofjan et al ( 24 ) and Gao et al ( 25 ). The main reason might be that the beneficial flora in the probiotic complex multiply in the intestine and constantly synthesized vitamins, amino acids and other beneficial substances, which are indispensable for the growth and development of the animal's immune organs.…”
Section: Discussionsupporting
confidence: 93%
“…The current study found that the addition of PC to the diet significantly increased the spleen index of AA+ broilers compared to the control group, and that the increase in thymus and bursa indices did not reach significant levels. This was also similar to the findings of Sjofjan et al ( 24 ) and Gao et al ( 25 ). The main reason might be that the beneficial flora in the probiotic complex multiply in the intestine and constantly synthesized vitamins, amino acids and other beneficial substances, which are indispensable for the growth and development of the animal's immune organs.…”
Section: Discussionsupporting
confidence: 93%
“…They are the main components of the micro ora in the gastrointestinal tracts of many animals. Many studies have shown that lactic acid bacteria can stably add value to a variety of animals by improving their immunity (Sjofjan et al 2021), reducing their pathogenic bacteria (Cisneros et al 2021), promoting their feed conversion rates (Yeh et al 2018), improving their growth rates, and reducing their feed:meat ratios. To reduce or eliminate the harm posed by antibiotics to food safety, many experts and scholars have studied lactic acid bacterial preparations to look for alternatives to antibiotics, and have used then in animal feed and for disease prevention, with good results (Gao et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Articles were identified from a systematic search performed on PubMed, Web of Science, Scopus, and Google Scholar databases as well as individual journals using the keywords “cassava”, “broiler chickens”, “feed intake”, “FCR”, “feed conversion efficiency”, “body weight gain”, or “ADG” ( 21 ). Reference lists of retrieved articles were screened for relevant studies.…”
Section: Methodsmentioning
confidence: 99%